2022
DOI: 10.3389/fneur.2022.839879
|View full text |Cite
|
Sign up to set email alerts
|

Stroke Related Knowledge, Prevention Practices and Associated Factors Among Hypertensive Patients at University of Gondar Comprehensive Specialized Hospital, Northwest Ethiopia, 2021

Abstract: IntroductionStroke is a global health problem, causing significant morbidities and mortalities in both developing and developed countries. Patients living with chronic diseases like hypertension are at a high risk of stroke. Approximately 80% of strokes could be prevented with necessary preventive practices. There is scarce evidence in the preventive practices in Ethiopia, particularly in the study area. Therefore, this study aimed to assess knowledge and prevention practices related to stroke among hypertensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 39 publications
(62 reference statements)
2
5
1
Order By: Relevance
“…The ndings of this study revealed that 42.9% of the participants had good knowledge of stroke prevention methods, within the 95% CI (38.4-48.0%), which is in line with the ndings of previous studies conducted in Ethiopia two studies in Gondar, 38.6 (18), 40.7% (13)and other counties, such as India (45.71%) (20). However, these ndings are greater than those of previous studies conducted in Ethiopia at Debre Tabor (24.9%) (21), South Gondar Zone (15%) and Uttar Pradesh, India (11.43%) (15).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The ndings of this study revealed that 42.9% of the participants had good knowledge of stroke prevention methods, within the 95% CI (38.4-48.0%), which is in line with the ndings of previous studies conducted in Ethiopia two studies in Gondar, 38.6 (18), 40.7% (13)and other counties, such as India (45.71%) (20). However, these ndings are greater than those of previous studies conducted in Ethiopia at Debre Tabor (24.9%) (21), South Gondar Zone (15%) and Uttar Pradesh, India (11.43%) (15).…”
Section: Discussionsupporting
confidence: 90%
“…This study revealed that the odds of physically active participants having good knowledge of stroke prevention were 4 times greater than those of participants who were physically inactive. These ndings are supported by the ndings of studies conducted in Ethiopia at Gondar Comprehensive Specialized Hospital (13) and in Sokoto, Nigeria (22). A possible explanation could be that health-conscious people are more likely to engage in bene cial health behaviours such as regular exercise because they tend to have a better understanding of their health, pay attention to individual health problems, and then take healthy measures to ensure their personal health.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…This finding was aligned with the earlier research concentrating on participants with high blood pressure, which reported that their knowledge level of warning signs and risk factors related to stroke was inadequate ( Bhat et al, 2021 , Houessou et al, 2021 , Melak et al, 2021 ). However, the proportion was lower than the previous research conducted among hypertension patients in Ethiopia (40.7%) ( Woldetsadik et al, 2022 ). One possible explanation for these findings is that most participants may have lacked information as a result of insufficient knowledge of stroke warning signs and risk factors.…”
Section: Discussioncontrasting
confidence: 73%